Romano-Celtic mask puzzle padlocks : a study in their design, technology and security - Slocum, Jerry (Archaeopress, 2017)
This book presents a little-known and ingenious artefact of the Roman world: a small puzzle padlock whose font plate bears a face or 'mask' of 'Celtic' style